High yielding, aromatic variety SEBERI 4 for irrigated lowland rice production systems in Niger - CGIAR Research Program on Rice (2020)
The variety was evaluated in multi-environment trials and then National Performance Trials and finally released as varieties SEBERI 4 by Niger in 2020.